Características da carne de cordeiros alimentados com glicerina proveniente da produção de biodiesel - Borghi, Thiago Henrique [UNESP] (2015)
This trial aimed to evaluate the physicochemical, sensory and nutritional characteristics of different muscles from lambs fed diets without and with glycerin inclusions, replacing corn. Thirty Ile de France non-castrated lambs with 45 days of age and about 15 ± 0,2 kg of body weight were confined in individual pens and slaughtered at 32 ± 0,2 kg. The treatments consisted of three diets: D0 - sugar cane + concentrate; D10 - sugar cane + concentrate + 10% glycerin and D20 - sugar cane + concentrate + 20% glycerin; and three muscles: Triceps brachii, Semimembranosus and Longissimus lumborum. No interactions were observed (P>0.05) between treatments and types of muscle in all the evaluated quality characteristics. The muscles of the lambs are similar in terms of physical-chemical, sensory and nutritional characteristics, so that only differ (P<0.05) in sarcomere length, diameter of muscle fibers and cholesterol content. The inclusion of glycerin in the diets of the lambs did not affect (P>0.05) the physicochemical characteristics pH, temperature, water holding capacity (24 hours and 30 days after slaughter), weight loss by thawing and cooking, strength shear, diameter of muscle fibers, sarcomere length, lipid oxidation, sensory attributes, chemical composition and meat cholesterol content. There were linear effect (P<0.05) with decrease on the variable b * (yellow intensity) of the muscles (3.79 to 3.09) and subcutaneous fat (8.20 to 7.02). In the fatty acid profile of the intramuscular fat, there were effects (P<0.05) of the glycerin inclusions, with increase in the concentration of heptadecanoic acid (1.64 to 2.61%) and sum of the fatty acids of the omega-family 3 (0.10 to 0.18%) and decrease in omega-6:omega-3 ratio (33.70 to 19.63). The inclusion of glycerin in the diet, replacing corn, did not affect the quality characteristics of the meat, confirming the possibility of using this co-product of the production of Biodiesel in ...